Isolating together during COVID-19: Results from the Telehealth Intervention Program for older adults - Sekhon, Harmehr; Lavin, Paola; Vacaflor, Blanca; Rigas, Christina; Cinalioglu, Karin; Su, Chien-Lin; Bodenstein, Katie; Dikaios, Elena; Goodman, Allana; Raymond, Florence Coulombe; Ibrahim, Marim; Bein, Magnus; et al. (Frontiers in Medicine, 2022)
Background: A pressing challenge during the COVID-19 pandemic and beyond is to provide accessible and scalable mental health support to isolated older adults in the community. The Telehealth Intervention Program for Older Adults (TIP-OA) is a large-scale, volunteer-based, friendly telephone support program designed to address this unmet need. Methods: A prospective cohort study of 112 TIP-OA participants aged ≥ 60 years old was conducted in Quebec, Canada (October 2020- June 2021). The intervention consisted of weekly friendly phone calls from trained volunteers. The primary outcome measures included changes in scores of stress, depression, anxiety, and fear surrounding COVID-19, assessed at baseline, 4 and 8-weeks. Additional subgroup analyses were performed with participants with higher baseline scores. Results: The subgroup of participants with higher baseline depression scores (PHQ9≥10) had significant improvements in depression scores over the 8-week period measured (mean change score= -2.27 (+/-4.76), 95%CI [-3.719, -0.827], p=0.003). Similarly, participants with higher baseline anxiety scores (GAD7≥10) had an improvement over the same period, which, approached significance (p=0.06). Moreover, despite peaks in the pandemic and related stressors, our study found no significant (p≥0.09) increase in stress, depression, anxiety or fear of COVID-19 scores. Discussion: This scalable, volunteer-based, friendly telephone intervention program was associated with decreased scores of depression, and anxiety in older adults who reported higher scores at baseline (PHQ 9 ≥10 and GAD7≥10).